A Comprehensive Exploration of Entrepreneurial Strategies in The Makeup and Beauty Industry: The Role of Social Media Marketing - Yupelmi, Mimi; Yulastri, Asmar; Ganefri; Giatman; Effendi, Hansi; Muskhir, Mukhlidi (The Indonesian Journal of Computer Science, 2023)
The research background is the rapid development of makeup and beauty industry in the social media era that is highly competitive. The study aims to explore the industry's development and its characters, the specialized entrepreneurial strategies, and the influence of social media on this industry. The methodology employed in this research is a semi-systematic literature review. The analytical approach utilized incorporates a meta-narrative framework, encompassing stages such as identifying, analyzing, and identifying patterns and themes related to the topic. The results describe that the characters of makeup and beauty industry includes highly competitive, ever-changing trends, consumer-centric, seasonal and limited-edition products, diverse product range. Furthermore, the role of social media and specialized entrepreneurial strategies related to the influencer collaborations, community building, personalized beauty, virtual beauty consultations, user-generated content, social commerce, online beauty classes, virtual events and live streams. Finally, the challenges of social media on entrepreneurial strategies associated with the policy and algorithm changes, negative feedback and criticism, data privacy and security.